(untitled) (Filološke pripombe, 2019)
The paper deals with corpus of Bulgarian, Croatian, Macedonian and Serbian idioms with the meaning ’never’. Idioms can be classified into three groups; the first group is motivated by days and holidays, in the second group impossible characteristics are attributed to the subject, while the third group consists of idioms with the component of time adverb. We analyse origins, motivation, semantics and their equivalence in both languages.